Vermögenspreise und Konsum: Neue Erkenntnisse, amerikanische Erfahrungen und europäische Herausforderungen - Gerhard Illing; Ulrich Klüh (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
– The article illustrates how the integration of modern theory of finance and stochastic dynamic macroeconomic analysis provides a deeper understanding of the link between asset prices and consumption. It shows that this approach gives only a partial explanation for recent trends in US consumption. Comparing wealth effects in Anglo Saxon countries with continental Europe, the paper provides a perspective of the challenges for European monetary policy arising from wealth effects on consumption.
urn:nbn:de:bvb:19-epub-316-8
Keywords: E21; E44; E58; 330; Wealth Effect; Consumption; Monetary Policy; Vermögenseffekt; Konsum; Geldpolitik